Mathematics Model on Syariah Share Pricing in ISSI - Jana, Padrul; Basri, Anindita Imam (Pendidikan Matematika Universitas PGRI Yogyakarta, 2020)
The ability to read, analyze data, and execute the Syariah economic market agents' decision becomes possible to happen. This research aims to help agents and those how to read the data, analyze, and model the data by providing perspectives regarding the stock pricing in the future. The research method being employed as Autoregressive Integrated Moving Average (ARIMA), which has steps of data plotting transforming, estimating the model, and forecasting. The results of this research found that ARIMA (1,1,0) is the best model of Syariah stock pricing on Indonesian Syariah Stock Indexing (ISSI). The test of model reliability employs RMSE, AIC, BIC/SBC, which is resulted in a fair, competitive suitable test to the employed model.Keywords: ARIMA, Mathematical Model, Forecasting, Stock